2022
DOI: 10.1371/journal.pgen.1010418
|View full text |Cite
|
Sign up to set email alerts
|

miR-275/305 cluster is essential for maintaining energy metabolic homeostasis by the insulin signaling pathway in Bactrocera dorsalis

Abstract: Increasing evidence indicates that miRNAs play crucial regulatory roles in various physiological processes of insects, including systemic metabolism. However, the molecular mechanisms of how specific miRNAs regulate energy metabolic homeostasis remain largely unknown. In the present study, we found that an evolutionarily conserved miR-275/305 cluster was essential for maintaining energy metabolic homeostasis in response to dietary yeast stimulation in Bactrocera dorsalis. Depletion of miR-275 and miR-305 by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…Deletion of miR-184-3p leads to termination of oocyte development [ 54 ]. Our previous study also found that the miR-275/305 cluster negatively regulated the transcription of SLC2A1/GLIS2 , eventually ensuring adult metabolic homoeostasis in B. dorsalis [ 55 ]. In this study, depletion of miR-2b-2-5p led to failure of lipid storage and ovarian development, whereas overexpression of miR-2b-2-5p resulted in lipid overaccumulation but displayed a similar reproductive phenotype as miRNA inhibition in B. dorsalis .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Deletion of miR-184-3p leads to termination of oocyte development [ 54 ]. Our previous study also found that the miR-275/305 cluster negatively regulated the transcription of SLC2A1/GLIS2 , eventually ensuring adult metabolic homoeostasis in B. dorsalis [ 55 ]. In this study, depletion of miR-2b-2-5p led to failure of lipid storage and ovarian development, whereas overexpression of miR-2b-2-5p resulted in lipid overaccumulation but displayed a similar reproductive phenotype as miRNA inhibition in B. dorsalis .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the expression level of miR-2b-2-5p was relatively low under starvation conditions compared with under feeding conditions. In a previous study, we found that the miR-275/305 cluster is regulated by the insulin signalling pathway in a nutrient-dependent manner [ 55 ]. Whether nutrient signalling, such as insulin or TOR signalling, is involved in the regulation of the miR-2b-2-5p/ CREB axis needs further study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations